All Days 2012
DOI: 10.2118/151868-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Shale Gas Exploration and Appraisal in Europe and North Africa

Abstract: The shale gas revolution on North America has created an incentive for the rest of the world to chase this challenging hydrocarbon resource. Currently around 44% of the 20.6 tcf annual gas production in the US occurs from unconventional resources, with this forecast to rise to 65% by 2020. The pitfalls and challenges faced by North American development projects provide a wealth of experience, which can be used to understand how we can apply technology more effectively in Europe and North Africa. However, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Insight from microfabric assessment indicate the existence of good petrophysical and geomechanical properties, which are desirable for gas shale development (Burns et al, 2012;Bouhlel et al, 2012).…”
Section: Implication For Unconventional Gas Developmentmentioning
confidence: 99%
“…Insight from microfabric assessment indicate the existence of good petrophysical and geomechanical properties, which are desirable for gas shale development (Burns et al, 2012;Bouhlel et al, 2012).…”
Section: Implication For Unconventional Gas Developmentmentioning
confidence: 99%
“…Choosing a suitable clay stabilizer in the process of filtering water is a common method to solve the reservoir damages caused by water sensitivity. [8,11,12] Research of clay stabilizers can be divided into three phases. [13] While the 1950s and 1960s were primary inorganic salts to stabilize clay, the 1970s was mainly inorganic multicore and cationic surfactants, and the research of organic cationic polymer was carried out since the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the interlayer spacing expansion and the volume expansion of the clays, which would directly reduce the cementation force and produce swelling force in rocks, are the most important internal factors for the loss of rock strength and indentation hardness. Over the past decades, the demands for effective shale stabilizers have never stopped. Especially, with the development of shale gas all over the world, such demands have never become as urgent as today …”
Section: Introductionmentioning
confidence: 99%